Advanced Game Design with HTML5 and JavaScript - van der Spuy, Rex (Springer, 2015)
How do you make a video game? Advanced Game Design with HTML5 and JavaScript is a down to earth education in how to make video games from scratch, using the powerful HTML5 and JavaScript technologies. This book is a point-by-point round up of all the essential techniques that every game designer needs to know.